Perceived effectiveness of the newly introduced method of fluid intake and output measurement by patients and watchers in the medical wards of a tertiary hospital - Almeda, Ma. Corazon; Awitan, Mary Annaces; Capistrano, Ma. Catherine; Decano, Kathleen; Dimaisip, Jed Asiaii; Galliguez, Merlyn; Impson, Grace; Mallorca, Karla Maree; Ortega, Paula Rhove; Rivera, Michael; Santos, Joseph Alvin; Sy, Eian Christian
Fluid balance monitoring, which Is one of the essential aspect of nursing care because It directs the course of the medical treatment of the patient, requires accurate and careful implementation. Fiwaver, past researches show that there are situations where intake and output measurements are filled with errors and Inaccuracies causing compromised patient outcomes. Therefore the purposes of this research Is to assess the current method of intake and output measurement in a tertiary hospital and to introduce an alternative method of intake and output measurement emphasizing the role and advantages of adequate health teaching. A quasi-experimental research design was utilized for this study. A total of 23 participants completed the questionnaire measuring previous knowledge of intake and output measurement and perceived effectiveness of the current method being used. The same participants were then subjected to health education about accurate and efficient Intake and output measurement. After the performance of the new desired behavior, the participants completed another questionnaire measuring the perceived effectiveness of the alternative method. The change between the pre-test score and post-test score was studied through Wilcoxon sign rank test. Findings showed only limited differences in test scores such that there is insufficient evidence to conclude that there is a statistically significant difference between the results of the pretest and posttest scores. However, scores in specific concepts pertaining to perceived importance and perceived efficiency of fluid balance monitoring, have significantly increased after the implementation of the alternative method. Factors undermining learning abilities of the patients need further Investigation. It is also suggested that the addition of health education and usage of patient perceived effectiveness be done to other aspects of health behavior in order to strengthen the current practice of heath care delivery.